mTOR Activation Is Required for the Antidepressant Effects of mGluR(2/3) Blockade - Dwyer, Jason M. (2011)
Recent studies demonstrate that ketamine, a fast-acting antidepressant, rapidly activates the mammalian target of rapamycin (mTOR) and increases synaptogenesis in the prefrontal cortex (PFC). Because of the side effect and abuse potential of ketamine we are investigating alternative agents that produce similar effects. Here we demonstrate that a single dose of LY341495, an mGluR(2/3) antagonist, produces ketamine-like biochemical and behavioral effects. LY341495 administration rapidly (1 hr) activates the mTOR pathway (mTOR, p70S6K, 4E-BP1) and subsequently (24 hrs) increases levels of synaptic proteins (PSD-95, GluR1 and Synapsin I) 24 hrs later, similar to the effects of ketamine. Finally, the antidepressant effects of LY341495 in the rat forced swim test are completely blocked by the mTOR inhibitor, rapamycin. The results indicate that the antidepressant actions of LY341495 are mediated by activation of mTOR and suggest that this and other mGluR(2/3) antagonists could produce rapid antidepressant effects in depressed patients.